Fermi-Bose duality of the Dirac equation and extended real Clifford-Dirac algebra - Krivsky, I.Yu.; Simulik, V.M. (Condensed Matter Physics, 2010)
We have proved on the basis of the symmetry analysis of the standard Dirac equation with nonzero mass that this equation may describe not only fermions of spin 1/2 but also bosons of spin 1. The new bosonic symmetries of the Dirac equation in both the Foldy-Wouthuysen and the Pauli-Dirac representations are found. Among these symmetries (together with the 32-dimensional pure matrix algebra of invariance) the new, physically meaningful, spin 1 Poincar ´e symmetry of equation under consideration is proved. In order to provide the corresponding proofs, a 64-dimensional extended real Clifford-Dirac algebra is put into consideration. На підставі симетрійного аналізу стандартного рівняння Дірака з ненульовою масою доведено, що це рівняння може описувати не лише ферміони зі спіном 1/2, але й бозони зі спіном 1. Знайдено нові бозонні симетрії рівняння Дірака як у представленні Фолді - Вотхойзена, так і у представленні Паулі - Дірака. Серед цих симетрій (поряд з 32-вимірною чисто матричною алгеброю інваріантності) доведено нову, фізично важливу симетрію Пуанкаре спіна 1 згаданого рівняння. Для виконання зазначених доведень введено в розгляд 64-вимірну розширену дійсну алгебру Кліффорда - Дірака.